2015
DOI: 10.1007/s10450-015-9708-2
|View full text |Cite
|
Sign up to set email alerts
|

Saw-sedge Cladium mariscus as a functional low-cost adsorbent for effective removal of 2,4-dichlorophenoxyacetic acid from aqueous systems

Abstract: For the first time in the published literature, a study is described concerning the use of the saw-sedge Cladium mariscus (C. mariscus) for adsorption of 2,4dichlorophenoxyacetic acid (2,4-D) from aqueous systems. Among the experiments carried out, the elemental composition of C. mariscus was determined (C = 48.0 %, H = 7.1 %, N = 0.95 %, S = 0.4 %), FTIR spectroscopic analysis was performed to confirm the chemical structure of the adsorbent, and porous structure parameters were measured: BET surface area (A B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A comparison of literature sorption capacities of different materials towards 2,4-D herbicide is presented in Table 4. Aminosilane-grafted mesoporous carbons are more effective adsorbents of 2,4-D than powdered activated carbons (Aksu and Kabasakal 2004), Cladium mariscus (Bartczak et al 2016), chitosan (Harmoudi et al 2014), chitin (Harmoudi et al 2014), blast furnace sludge (Gupta et al 2006), blast furnace dust (Gupta et al 2006) or modified silica gel (Koner et al 2013). This high adsorption capacity could be ascribed to the unique properties of carbon materials obtained (Goscianska and Olejnik 2018).…”
Section: Adsorption Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…A comparison of literature sorption capacities of different materials towards 2,4-D herbicide is presented in Table 4. Aminosilane-grafted mesoporous carbons are more effective adsorbents of 2,4-D than powdered activated carbons (Aksu and Kabasakal 2004), Cladium mariscus (Bartczak et al 2016), chitosan (Harmoudi et al 2014), chitin (Harmoudi et al 2014), blast furnace sludge (Gupta et al 2006), blast furnace dust (Gupta et al 2006) or modified silica gel (Koner et al 2013). This high adsorption capacity could be ascribed to the unique properties of carbon materials obtained (Goscianska and Olejnik 2018).…”
Section: Adsorption Studiesmentioning
confidence: 96%
“…It was found that removal of 2,4-D by carbon adsorbents at the initial stage increased with an increase in pH from 2 to 3, then remained almost unaffected up to pH of 5. Further increase of pH in the range from 7 to 11 led to a decrease in sorption capacity of materials towards 2,4-D. Because of low pKa value (2.73) of herbicide, it exists predominantly in anionic form (Bartczak et al 2016;Koner et al 2013). In acidic solutions the aminosilane-grafted mesoporous carbons become more positively charged which results in greater adsorption of anionic species.…”
Section: Adsorption Studiesmentioning
confidence: 99%
See 3 more Smart Citations